Analisis Beban Kerja Fisiologis dan Mental Mahasiswa pada Simulasi Lingkungan Kerja di Laboratorium Ergonomi Menggunakan Pendekatan Macroergonomics Analysis of Structure - Firdaus, Aqfi Nur; Yasin, Nurnianingsih A; Daud, Parlan S; Mohamad, Silvana; Bukamo, Richard Renaldy (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study analyzes the physiological and mental workload of students in a simulated work environment at the Ergonomics Laboratory using the Macroergonomics Analysis of Structure (MAS) approach. The simulation exposed 21 participants to a combination of grinding machine noise (90 dB) and low lighting (10 Lux) for 40 minutes. The results indicate that the simulated work environment significantly increased physiological workload, evidenced by an increase in pulse rate where 38% of participants exhibited a %CVL above 15% (category